Correlation between TV's ads, demographic factors and Children Materialism - Utama, Wahyu Satria; Ulfa, Nurist Surayya; Herieningsih, Sri Widowati; Rahardjo, Turnomo (Interaksi Online, 2016)
This study concerns about children’s materialism. TV’s advertising is acknowledged to be an extensive carrier of materialism. Previous research said demographic factors like gender, age and SES are influencing children’s materialism. Based on survey to 96 children age 12-14 years old in Semarang, Indonesia, the findings indicate TV’s advertising and demographic factors influences materialism on children. This study showed exposure of TV’s advertising and demographic factors are significant to children’s materialism.